Individualised monitoring of patients with metastatic melanoma using plasma DNA. (23rd February 2017) - Wan, Jonathan; Murphy, Suzanne; Gale, Davina; Morris, James; Mouliere, Florent C; Marass, Francesco; Heider, Katrin; Chandrananda, Dineika; Bignell, Graham; Parkinson, Christine; Durrani, Amer; McDermott, Ultan; et al.
Abstract: Background: Circulating tumour DNA (ctDNA) is released by cancer cells into the bloodstream, which can be analysed via liquid biopsy. Analysis of liquid biopsy samples provides a real-time snapshot of tumour burden. After treatment, ctDNA concentrations can be low, making detection challenging. To study clonal evolution during treatment in patients with melanoma with high sensitivity, we sought to maximise the number of mutations targeted through individualised next-generation sequencing panel design. Methods: 72 patients with stage III or IV melanoma were recruited to MelResist, a translational, multicentre research study. Serial plasma samples were taken from patients at monthly intervals during treatment (median 6·7 samples per patient). Clinical events were scored according to Response Evaluation Criteria In Solid Tumors (RECIST) (version 1.1) criteria. Exome and targeted sequencing were carried out on tumour samples at baseline and progression for nine patients, whose identified mutations were used to design an individualised targeted sequencing panel. Findings: Multiple mutations per patient were tracked to monitor response to therapy. The percentage change in ctDNA mutant allele fraction after treatment initiation agreed with RECIST response for seven out of eight evaluable patients. ctDNA concentration strongly correlated with lactate dehydrogenase (LDH) concentration, a currently used measure of melanoma tumour burden ( r 2 =0·64, p=9·93 × 10 −7 ). ctDNA dynamics were compared against rising LDH, which showed a median lead-time to biochemical progression (rising LDH) of 70 days (IQR 28–152·3). Targeting multiple mutations could improve sensitivity compared with individual mutations. Interpretation: In this study, we applied an individualised targeted sequencing panel on ctDNA from patients with melanoma. As tumour sequencing becomes more routine, individualised sequencing panel design might become more feasible, facilitating a more sensitive approach for ctDNA analysis than targeting individual loci. Tracking clonal evolution during therapy non-invasively may facilitate personalised treatment decisions with molecularly targeted agents. Funding: Cancer Research UK, Lewis Family Charitable Trust, Addenbrooke's Charitable Trust, Cambridge Cancer Trials Centre, NIHR Cambridge Biomedical Research Centre and Human Research Tissue Bank.